Sri Lankan Tamil Writer’s Concern for the safety of the Environment: A Study on Selected Tamil stories in English - Shriganeshan, K. (University of Jaffna, 2016)
There is an urgent need for institutional reform within modern society to safeguard the environmental resources and to maintain the ecological balance for a greener future. Many wars which the world has seen have caused a lot of damages to the environment. The war between the Sri Lankan forces and the Tamil militants held in the last decade of the Twentieth century and the first decade of the Twenty-first century has made a negative impact on the lives of the people. This is more evident in the pieces written by Sri Lankan Tamil writers available in translation. This paper tries to look into four short stories originally written in Tamil by Tamil and Muslim writers and translation into English by S.Sivasekaram, S.Pathmanathan and A.J.Canagaratne. They appeared in collections edited by Chelva Kanaganayakam(2001), Ashley Halpe, M.A.Nuhuman and Ranjini Obeyesekara,(2002) and S.Pathmanathan(2013). A critical analytic approach is adopted to see how these stories are able to capture the characters trapped in conflict struggle in the environmental crisis created by the war. This paper attempts to highlight the writers’ concern about the safety of the environment and critically analyse the stories to show how the writers are more concerned about the safety of the environment
Keywords: Institutional reform; Environmental crisis; Writers’